Cryopreservation as Optimizing Factor in Therapeutic Effect of Products of Embryofetoplacental Complex (PEFPC) Part II. Fetal Liver Cell Correction of Lymphohemopoietic Complex State in Experimental Animals with AIHA - Goltsev, A. N.; Popova, K. N.; Sirous, M. A. (Problems of Cryobiology and Cryomedicine, 2006)
Therapeutic efficiency of fetal liver cells (FLCs) of different gestation terms when treating autoimmune hemolytic anemia (AIHA) has been evaluated. The fact of manifested correcting effect of FLCs in respect of different compartments of lymphohemopoietic complex (LHPC) in AIHA animals has been established. Manifestation extent of FLCs activity was shown to be determined by gestation term and material type. When summarising therapeutic effect according to all evaluated systems there was demonstrated that FLCs of certain gestation terms gained higher level of integral therapeutic potential following cryopreservation.